Research on Change Management into Small Family Businesses - Eduard CEPTUREANU (Revista de Management Comparat International)
In this paper we analyse the impact of family involvement over change into Romanian small family businesses. Accordingly, we have contributed to entrepreneurship generally and family SMEs studies particularly by testing the relationship between family involvements and change. In addition we develop family business theory and entrepreneurship by testing variables as sources of change among family business. Our findings present a broader perspective of Romanian entrepreneurial landscape from family business concepts.